Genetic Variants of C-5312T REN Increased Renin Levels and Diastolic Blood Pressure Response to Angiotensin Receptor Blockers - Mohammad Saifur Rohman; Ika Arum Dewi Satiti; Nashi Widodo; Mifetika Lukitasari; Hidayat Sujuti (International Journal of Hypertension)
Renin catalyzes the cleavage of angiotensinogen into angiotensin I. Genetic variant C-5312T of renin enhancer has been reported to increase in vitro renin gene transcription. However, no obvious in vivo study was performed to see the renin level in C-5312T when treated with angiotensin receptor blockers (ARB). Therefore, this study aimed to investigate the serum renin level and blood pressure response in ARB treated hypertensive patients. Single nucleotide polymorphism (SNP) of C-5312T was identified in 55 hypertensive patients by using multiplex PCR and renin serum level was assayed by ELISA. The data showed that the increase of serum renin levels after 5 months of ARB treatment was significantly higher in patients with CT/TT genotype (10 pg/mL) than those with CC genotype (4.08 pg/mL) (P = 0.025). Hypertensive patients with CT/TT genotypes also showed less diastolic pressure reduction than CC genotypes in hypertensive patients with valsartan treatment (P = 0.04) or telmisartan treatment (P = 0.03). Finally, these findings suggested that SNP of C-5312T REN enhancer might contribute to higher increased renin serum levels and less diastolic blood pressure response to ARB treatment.